Steam oxidation of heat exchanger materials for the new generation of power plants. - Bouvet, Justin (Cranfield University, 2018)
Energy production over recent decades has emitted CO2, linked to an increase in global average temperatures and climate change. Part of the solution to tackle this is through improved power plant flexibility to enable renewable integration, and enhanced generator efficiency. Fossil fuel-based generators’ efficiencies can be improved by increasing steam working temperatures and pressures inside power plants. However, these more severe working conditions can accelerate degradation phenomena, for example, by steam oxidation. To assess the simulate steam oxidation processes at the elevated temperatures required for high efficient power plants, various austenitic steels and nickel-based alloys were exposed to pure steam between 650 and 800°C for up to 10,000 hours. Effects of pressure and surface finish were also investigated. It was observed that, for the different materials, oxide formation increased with increasing oxidation time and steam temperature. Oxidized TP347HFG samples (18.4%wCr and 11.5%wNi) exhibit multi-layered oxide scales susceptible to spallation. Surface finishes applying high compressive stresses drastically enhanced oxidation resistance and promoted chromia layer formation even at elevated temperatures and longer exposure times. Other prepared surfaces, with low compressive stresses, induced increased oxidation resistance only at early exposure times. Sanicro 25 (22.5%wCr and 25%wNi) and nickel-based alloys naturally possess very high oxidation resistances, which results from ready formation of chromia formation on their surfaces; these alloys were not affected by surface preparation. Exposing different materials to increasing pressure in laboratory experiments increased oxidation rates. However, in service exposed materials show the opposite pressure effect. Isotope exposure tests revealed that up to 20% of the anionic species in the oxide layers were hydroxides and/or hydrogen, showing their significant influence on the steam oxidation mechanisms. Finally, models describing mass change and oxide growth for the different materials and surface finishes were developed to contribute to better power plant management.
Keywords: Pure steam; surface finish; high temperature; pressure effect; isotope exposure; ferritic steels; austenitic steels; nickel-based alloys